2017
DOI: 10.18584/iipj.2017.8.4.8
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Indigenous and Western Knowledge Systems (Part 2): “You Have to Take a Backseat” and Abandon the Arrogance of Expertise

Abstract: Despite innovative technological "solutions" to address ongoing water crises in Indigenous communities, significant disparities persist in Canada. Financial investment in infrastructure is necessary, but it is hardly sufficient to address the real problem: entrenched colonialism. One of the greatest challenges in decolonizing research is to prevent that research from reproducing the very categories it is seeking to critique and dismantle. We share findings from thematically-analyzed interviews with academic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 26 publications
1
39
0
Order By: Relevance
“…If a monitoring system is community-led and communitybased, there is a need to consider whether co-authorship is appropriate, recognizing that some community members may request not to be authors for a variety of reasons. Nevertheless, steps need to be taken to avoid risks including tokenistic inclusion, implied support for findings, and misappropriation of knowledge [104,106]. Multiple evidence-based (MEB) approaches offer a way forward for Indigenous and non-Indigenous collaborators to work together in developing CBM systems that respects and reflects different contributions [107].…”
Section: Externally Driven Monitoringmentioning
confidence: 99%
“…If a monitoring system is community-led and communitybased, there is a need to consider whether co-authorship is appropriate, recognizing that some community members may request not to be authors for a variety of reasons. Nevertheless, steps need to be taken to avoid risks including tokenistic inclusion, implied support for findings, and misappropriation of knowledge [104,106]. Multiple evidence-based (MEB) approaches offer a way forward for Indigenous and non-Indigenous collaborators to work together in developing CBM systems that respects and reflects different contributions [107].…”
Section: Externally Driven Monitoringmentioning
confidence: 99%
“…One tangible way the IISD-ELA (and others) may want to think about working within Western scientific and Indigenous knowledge realms is Etuaptmumk (or Two-Eyed Seeing)-a Mi'kmaw principle arising from the teachings of Elder Albert Marshall of Eskasoni First Nation (Canada), which may help prevent us from 'forcing' IK into Western paradigms of water science (Castleden et al 2017b. In summary of the idea, Marshall describes that we must learn to:…”
Section: Discussionmentioning
confidence: 99%
“…Such analysis may require additional information and data collection. For example, recognizing the limitations of available information in published studies, particularly with regard to process, [63] built upon a systematic realist review by conducting semi-structured qualitative interviews with the first authors and community participants of exemplar cases identified via the review.…”
Section: Evidence Gaps and Insightsmentioning
confidence: 99%